StarTRAC-CYP2D6: a method for CYP2D6 allele-specific copy number determination using digital PCR - Wang, Wendy Y.; Boone, Erin C.; Lin, Lancy; Joun, David; Gaedigk, Andrea (Frontiers in Pharmacology, 2025)
BackgroundAccurate CYP2D6 genotyping is essential for pharmacogenetic-guided prescribing of many clinically used medications. While digital PCR is increasingly used to determine copy number (CN) status for accurate phenotype prediction, there are few convenient methods to discriminate duplicated alleles and diplotypes such as CYP2D6*2/*4x2 and *2x2/*4, which predict intermediate and normal metabolizer phenotypes, respectively. We developed a novel method, StarTRAC-CYP2D6, “Targeted Reporting of Allele-specific CNV”, for determining the number of specific CYP2D6 star allele copies. Additionally, we explored the impact of DNA input and interfering variants on CN assay performance.MethodsCoriell samples (n = 17) representing various CYP2D6 star alleles and structural variants were tested on the QuantStudio™ Absolute Q™ Digital PCR System using the previously established research use only one-pot workflow and seven multiplexed TaqMan™ genotyping assays. Each multiplex targets a core variant found in commonly observed gene duplications: g.100C>T, g.1022C>T, g.1847G>A, g.2851C>T, g.2989G>A, g.3184G>A, and g.4181C. The multiplex contains targeted genotyping probes labeled with FAM, VIC and JUN, and either RNaseP or TERT labeled with ABY, serving as 2-copy gene references.ResultsThe CN of the specific alleles represented in this study include: CYP2D6*1, *2, *4, *10, *17, *29, *41, *45, *36, *68, *154, and *158. Allele-specific CN ranging from 0 to 4 copies were reliably resolved. All samples with duplications/multiplications were accurately discriminated with their expected star allele. For CN up to 6 copies, a total DNA input of 200 ng maintained CN integrity and variants interfering with primer/probe binding had a range of effects on CN determination.ConclusionStarTRAC-CYP2D6 is an effective, stand-alone method for determining the CN of specific star alleles. DNA quantity and possible interfering variants should be considered when optimizing workflows and accurately interpreting results. Protocols are currently being developed for higher-plex CN testing and discrimination.